Tax exemption for biofuels in Germany: Is bio-ethanol really an option for climate policy? - Jan Michael Henke; Gernot Klepper; Norbert Schmitz (Kiel Institute for World Economics (IfW), 2003)
Last year the German Parliament exempted biofuels from the gasoline tax. The promotion of biofuels is being justified by allegedly positive effects on climate, energy, and agricultural policy goals. The paper takes a closer look at bio-ethanol as a substitute for gasoline. We analyze the basic conditions that provide the setting for the production and promotion of biofuels and show that the production of bio-ethanol in Germany is not competitive. Using energy and greenhouse gas balances we demonstrate that a possible increased use of bioethanol to reduce greenhouse gas emissions is inefficient and that there are preferred alternative strategies. In addition, scenarios on the development of the bio-ethanol market are derived from a model that allows for variations in decisive variables and reflects the production and trade chain of bio-ethanol.
Keywords: D61; H23; Q25; Q42; 330; biofuels; ethanol; climate policy; agricultural policy; gasoline tax; energy balances; GHG balances; Biokraftstoff; Mineralölsteuer; Steuerbegünstigung; Steuerwirkung; Klimaschutz; Stoffstrom-Management; Deutschland